The functional and radiological comparison of the surgical treatment results of forearm diaphyseal fractures in adults treated with open reduction internal fixation and intramedullary locking nail - Çevik, Nazan; Akalın, Yavuz; Öztürk, Alpaslan (The European Research Journal, 2020)
Objectives: The results of two different methods applied in the surgical treatment of forearm fractures in adults were evaluated.Methods: Thirty-nine patients who applied to our clinic between 2016-2018 and were treated surgically were included in the study. Twenty-three patients out of these were treated with plate osteosynthesis (group 1), and 16 patients were treated with intramedullary locking nail (group 2). While 14 of the patients in group 1 were male, 9 were female, and the average age was 39.8 years (range; 19-74 years); and 11 of the patients in group 2 were male, 5 were female, and the average age was 36.6 years (range; 18-68 years). Patients were called for monthly check-ups until fracture union. Then, radiographic evaluation was done at 3, 6 and 12 months. The average follow-up time was 26 months (range;12-36 months) for group 1 and 25 months (range;12-35 months) for group 2. The loss of the line of fracture through radiographic imaging of trabeculations or callus formation in the cortex on the anteroposterior and lateral radiographs, and clinically loss of sensitivity on fracture were considered fracture union. In the last controls, while the elbow was at 90 degrees of flexion, the amount of rotation of both forearms was measured by using the goniometer. In the functional evaluation, the system described by Grace and Eversmann and used to evaluate fracture union and forearm rotation was used. Patient satisfaction was evaluated by using the DASH (Disabilities of the Arm, Shoulder and Hand) method.Results: While the union duration in group 1 was 12.3 weeks (range; 8-18 weeks), the union duration in group 2 was 12 weeks (range; 9-16 weeks). There was no statistical difference in terms of union durations (p > 0.05). In Group 1, according to the Grace-Eversmann evaluation, 19 (82.6%) patients had excellent and good results, three (13.1%) patients had acceptable results, and 1 (4.3%) patient had poor results. Forearm pronation of the patient with poor results was less than 60% but his bone union was complete. In group 1, the average DASH score was 15.04 (range; 3-28). In group 2, Grace-Eversmann evaluation showed excellent and good results in 13 (81.3%) patients and acceptable results in 3 (18.7%) patients. Average DASH score was found to be 14.6 (range; 2-34). When Grace-Eversmann criteria and DASH values were compared, no significant difference was found between the two groups (p > 0.05). Vascular nerve injury, tendon injury, radioulnar synostosis, and compartment syndrome were not observed in any patient.Conclusions: The results of the two fixation methods in terms of functional recovery and patient satisfaction were similar in the surgical treatment of forearm double fractures in adults.